Post Program Monitoring During The Pandemic : Proposal For Temporary Streamlining Of Procedures And Renaming Of The Policy. (Policy Papers; Policy Paper ;, 2021)
The increase in Fund lending in the aftermath of the Covid-19 pandemic, including emergency financing, has led to a record number of requests for financing last year, and to an unprecedented amount of credit outstanding. This underscores the need for appropriate safeguards to the Fund's balance sheet. Post Program Monitoring (PPM) is one such safeguard, which provides a framework for deeper and closer engagement with members that have substantial outstanding Fund credit but are not in a program relationship.